Poverty alleviation programmes reduce inequities in health : evidence from Bangladesh* - Chowdhury, A Mushtaque R (BRAC Research and Evaluation Division (RED), 2019)
Over the previous two decades many poverty alleviation programmes have been implemented in developing countries. Evaluation of such programmes have traditionally looked at their success in increasing the income levels of participants but less on the broader goals of human well-being. This chapter looks a~ the poverty alleviation programme of BRAe, a large non-governmental organization in Bangladesh, and, based on a scientifically designed study, presents its impact on selected components of 'human well-being'. The study found better child survival and nutritional status in households served by the programme. Similar impacts were also found in other areas such as expenditure pattern, family planning practice and children's education. The likely influence of 'selectively bias ' on the above results is also discussed